The Effectiveness Comparison of Aloe Vera and Nothopanax Sutellarium Extract Toward Thermal Burn on White Rat (Rattus Norvegicus) - Nasution, Sri Lestari Ramadhani; Revina, Monica; Yuliani, Riski; Nasution, Sri Wahyuni (Journal of Education, Health and Sport, 2019)
Thermal burn is depicted as tissue damage which is caused by heat contact, chemical material, electricity and radiation. Several herbal materials that can be used as burn healing are Aloe Vera and Nothopanax Scutellarium. This study is aimed to find out the effectiveness comparison between 50% and 70% concentration on each herbal materials. The sample that used is 30 white rats (Rattus Norvegicus) which is chosen according to the inclusion criteria, and will be divided into 6 groups in which each of groups are given different treatment including: positive control, negative control, 50% formulation of N. scutellarium extract ointment, 75% N. scutellarium, and 50% A. vera. The extract formulation is obtained using maceration method using 96% ethanol solvent, and then the extract will be formulated to be A. vera extract ointment and N. scutellarium with 50% and 75% concentration. The withe rats which given thermal burn treatment will be applied using ointment extract, and it will be left out and observed every three days. Afterward, from the results, the significant will be assessed using ANOVA method. Thus, the results show that A. vera has p = 0,045 and N. scutellarium has p = 0,038 and for both of them are p < 0,05. The T significance then assessed by the result of A. vera extract and N. Scutellarium are p = 0,000 and p < 0,005, respectively. Hence, from the result of assay, the smallest level of burn severity is on N. scutellarium extract, therefore it can be said as the most effective for wound healing with 75 % concentration than A. vera.